Pay up! Equal pay for women - TGWU leaflet, 2002 (2002)
2002 1960-2000 "Pay up! Equal pay for women - TGWU leaflet, 2002" [EP0184], 2002 In 1999, the Equal Opportunities Commission set up an Equal Pay Task Force. In a report published in 2001, the Task Force recommended that employers should conduct audits to assess the extent to which their organizations had made progress towards implementation of equal pay. This leaflet from the Transport and General Workers' Union encourages members to carry out pay audits in the workplace.